Positive emotions from social company in women with persisting subclinical psychosis: lessons from daily life. (4th June 2013) - Collip, D.; Wigman, J. T. W.; van, J.; Oorschot, M.; Jacobs, N.; Derom, C.; Thiery, E.; Peeters, F.; Wichers, M.; Myin‐Germeys, I.
<x xml:space="preserve">Abstract</x> Objective Altered social reward functioning is associated with psychosis irrespective of stage and severity. Examining the role of social reward functioning prospectively in relation to psychotic experiences before these become persistent and potentially disabling can aid in elucidating social mechanisms that induce shifts toward more severe psychotic states, without the confounding effects of clinical disorder. Method In a longitudinal general population sample (N = 566), the experience sampling method (repetitive random sampling of momentary emotions and social context) was used to assess daily life social functioning at baseline. Persistence of subclinical psychotic experiences was based on the Community Assessment of Psychic Experiences assessed three times over 14 months. Analyses examined to what degree i) social context and ii) appreciation thereof differentiated between those who did and did not develop persistent psychotic experiences. Results Although individuals with persistent psychotic experiences did not differ in overall level of positive effect, the amount of time spent alone or the level of social satisfaction compared to individuals without persistent psychotic experiences, they were more sensitive to the rewarding effects of social company. Conclusion Alterations in social reward experience may form one of the mechanisms that precede the development of the extended psychosis phenotype over time.